Henoch-Schönlein purpura in adults is not uncommon in elderly patients with an adverse prognosis - Schaier, Matthias; Freitag, J.; Dikow, Ralf; Sommerer, Claudia; Groß-Weissmann, Marie-Luise; Waldherr, Rüdiger; Andrassy, Konrad; Zeier, Martin; Schwenger, Vedat (Clinical nephrology, 2011)
Background: Henoch-Schönlein purpura (HSP) is a fairly common disease in children and adolescents. There are only limited data available for adults. Methods: A retrospective analysis was conducted to study renal manifestations in patients with HSP treated in our institution between 1982 and 2007. We divided our adult cohort according to age – under or over 60 years – to examine differences in elderly patients. Results: HSP was identified in 2.2% of patients referred to us for kidney biopsy. Purpuric lesions and renal involvement were found in all patients. An important triggering factor for the development of HSP in our series was chronic alcohol intake. Forty percent of our patients fulfilled the WHO criteria for alcoholics. Renal involvement was particularly prominent in patients over 60 years of age. At disease onset, estimated glomerular filtration rate (eGFR) was 63% lower in the elderly. Within a median follow-up of 8 years, renal function was significantly better in younger adults than in the elderly. 32% of the elderly have shown Modification of Diet in Renal Disease (MDRD) < 20 ml/min/1.73 m2 in contrast to only 7% in patients < 60 years. Furthermore, significantly more elderly patients reached end-stage renal failure. Conclusion: The data indicate that renal manifestation of HSP in the elderly is severe and its outcome relatively poor, and worsens when compared to patients < 60 years.
Gesehen am 07.10.2022